An azimuth cut-off wavelength compensation method based on multiview synthetic aperture radar synchronization data. Issue 3 (3rd March 2020) - Wan, Yong; Zhang, Xiaoyu; Dai, Yongshou; Shi, Xiaolei
ABSTRACT: Focusing on the azimuth cut-off wavelength problem of ocean waves observed by a single synthetic aperture radar (SAR), we proposed an azimuth cut-off wavelength ( λ c ) compensation method based on multiview SAR ocean wave synchronization data, which could be obtained by cooperative observations from networked SAR satellites. However, multiple in-orbit SAR satellites cannot simultaneously observe the identical ocean, and multiview ocean data cannot be acquired. Thus, this paper first simulated a satellite network comprising three SAR satellites and sea wave synchronization data from those satellites. Based on these data, the optimized wave spectrum of each SAR observation was obtained by inversion with the Max Planck Institute (MPI) algorithm, and λ c was estimated accordingly. According to the spectral data fusion method designed in this letter, the optimized wave spectrum was fused, and the λ c value after fusion was estimated. The results show that the λ c value after fusion was smaller than the prefusion value, and the effect of the cut-off wavelength was weakened. Consequently, the proposed λ c compensation scheme for multiple SARs is effective.